EFFECT OF UPSTREAM SIDE SLOPE OF CRUMP WEIR ON DISCHARGE COEFFICIENT - Hayder Abbas Al-Yousefi; Ali Abbas Kadhem; Layth Abdul Rasool ALASADI (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The current study examines the flow characteristics under free flow conditions over a crump weir. The impact of the side slopes of the weir on the coefficient of discharge (Cd) is taken into account. Four physical models with crest heights of 0.15 m under free flow circumstances and four upstream side slope (1:3, 1:2.5, 1:2 and 1:1.5) were used to investigate the impact of various variables on discharge coefficient (Cd). Using the dimensional analysis technique, the elements influencing the crump weir's discharge coefficient were determined based on laboratory tests. For the same flow rate, Cd value decrease by decreasing upstream side slope. It notices that a decrease in upstream slope (from 1:3 to 1:2.5) reducing Cd value about (2.61 %), decrease upstream slope from (1:3 to 1:2) reducing Cd value about (4.16 %) and when decrease upstream slope from (1:3 to 1:1.5) reducing Cd value about (5.81 %).